Synthesis and characterization of cellulose acetate from cellophane industry residues. Application as acetaminophen controlled-release membranes - Ribeiro, Sabrina Dias; Meneguin, Andréia Bagliotti [UNESP]; Barud, Hernane da Silva; Silva, Jhonatan Miguel; Oliveira, Rafael L.; Asunção, Rosana Maria Nascimento de; Tormin, Thiago Faria; Muñoz, Rodrigo Alejandro Abarza; Filho, Guimes Rodrigues; Ribeiro, Clovis Augusto [UNESP] (Springer Nature, 2021)
Cellophane film production generates cellulosic residues from scraps, edges, and low-quality films. In this work, cellophane was used as a raw material to produce cellulose acetate (CA). CA was produced through the homogeneous route for 6 to 24 hours producing materials with a degree of substitution (DS) between 2.6 and 2.9. The CA materials were characterized by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), X-ray diffraction (XRD), and viscosity-average molecular weight. DS values (DS > 2.6) indicate the preferential formation of cellulose triacetate, and the reaction time leads to materials with different molecular weight from 32,000 to 121,000 g mol- 1 The TGA and DSC curves allowed obtaining information that, together with other techniques, confirm the formation of cellulose triacetate and the production of a material with a heterogeneous structure. The CA membrane was prepared with CA produced with 14 hours of the reaction intended to control the release rates of acetaminophen (ACP). A dense, seemingly pore-free membrane has been produced, as seen by SEM images, which allows the release of small amounts of ACP. The results were promising in the development of CA membranes for the controlled release of drugs from the chemical modification of cellophane residues.
Keywords: Cellophane; Cellulose acetate; Controlled release; Homogeneous reaction; Industrial waste; Thermal behavior